Sterilization and properties of braided silk surgical thread - Tashmetov, M.Yu.; Ismatov, N.B.; Saidov, R.P.; Mahkamov, Sh.M.; Abdulmanov, R.G.; Xabibullaev, X.R. (Вопросы атомной науки и техники, 2015)
The radiation treatment carried out of surgical braided silk thread at the electron accelerator "Electronics U-003." The value of sterilization dose and dependence of breaking load of braided surgical silk thread and a simple surgical knot from absorbed dose is determined. The dependence of the elastic modulus of the thread from the absorbed dose is established. Здійснена радіаційна обробка плетеної хірургічної шовкової нитки на прискорювачі електронів "Електроніка У-003". Встановлено значення стерилізаційної дози і залежність розривного навантаження плетеної хірургічної шовкової нитки і простого хірургічного вузла від поглиненої дози. Встановлена залежність модуля пружності нитки від величини поглиненої дози. Осуществлена радиационная обработка плетенной хирургической шелковой нити на ускорителе электронов "Электроника У-003". Определено значение стерилизующей дозы и зависимость разрывной нагрузки плетенной хирургической шелковой нити и простого хирургического узла от поглощенной дозы. Установлена зависимость модуля упругости нити от величины поглощенной дозы.